Gender equality and gender norms: framing the opportunities for health. Issue 10190 (22nd June 2019) - Gupta, Geeta Rao; Oomman, Nandini; Grown, Caren; Conn, Kathryn; Hawkes, Sarah; Shawar, Yusra Ribhi; Shiffman, Jeremy; Buse, Kent; Mehra, Rekha; Bah, Chernor A; Heise, Lori; Greene, Margaret E; et al.
Summary: The Sustainable Development Goals offer the global health community a strategic opportunity to promote human rights, advance gender equality, and achieve health for all. The inability of the health sector to accelerate progress on a range of health outcomes brings into sharp focus the substantial impact of gender inequalities and restrictive gender norms on health risks and behaviours. In this paper, the fifth in a Series on gender equality, norms, and health, we draw on evidence to dispel three myths on gender and health and describe persistent barriers to progress. We propose an agenda for action to reduce gender inequality and shift gender norms for improved health outcomes, calling on leaders in national governments, global health institutions, civil society organisations, academic settings, and the corporate sector to focus on health outcomes and engage actors across sectors to achieve them; reform the workplace and workforce to be more gender-equitable; fill gaps in data and eliminate gender bias in research; fund civil-society actors and social movements; and strengthen accountability mechanisms.